Pengaruh Pemberian Pupuk Organik Padat dari Limbah Burung Puyuh Dengan Dosis Berbeda terhadap Pertumbuhan Tanaman Odot ( Pennisetum Purpureum Cv. Mott ) - Mohammad Ali Yusuf Setiawan; Erna Yuniati; Ardina Tanjungsari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to determine the effect of applying solid organic fertilizer derived from quail waste at different dosages on the growth of Pennisetum purpureum cv. Mott (Odot elephant grass). It also aimed to analyze the macronutrient content (N, P, K) in the soil after treatment and to ensure that the solid organic fertilizer met the quality standards according to SNI (Indonesian National Standard).The study used a Randomized Block Design (RBD) with four treatments and three replications. The treatments consisted of: no quail manure with 100% urea fertilizer (P0), 25% quail manure + 75% urea fertilizer (P1), 50% quail manure + 50% urea fertilizer (P2), and 75% quail manure + 25% urea fertilizer (P3). The observed growth parameters of Odot grass included plant height, number of leaves, leaf length, fresh weight, and dry weight. The observed soil parameters included soil conditions before planting and after planting, namely N, P?O?, and K?O. The parameters of organic fertilizer content observed included N, P?O?, and K?O. Analysis of variance (ANOVA) was used to analyze the research data. The results showed that the application of quail manure fertilizer had a significant effect on the growth of Odot grass in terms of plant height, number of leaves, and leaf length. However, it did not show a significant effect on fresh weight and dry weight. The highest average plant height was found in treatment P2 (615 cm), the highest average number of leaves in P1 (83 leaves), and the highest average leaf length in P2 (67.3 cm). Meanwhile, fresh weight was not significantly affected, with the highest average found in P2 (476.67 g), and dry weight with the highest average in P1 (181.67 g).